Estimating Unsaturated Hydraulic Conductivity of Cocopeat-Perlite Mixtures Using RETC Software (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Cocopeat in soilless culture needs to be mixed with other coarser substrate to increase aeration medium. Hydraulic conductivity is fluid ability measurement to flow through pore spaces happens in saturated and unsaturated conditions. This study focused to estimate cocopeat-perlite unsaturated hydraulic conductivity using RETC software. 6 treatments were used, 100% cocopeat act as control treatment (T1), while treatments with different cocopeat-perlite ratio (T2=3 cocopeat:1 perlite;T3=2 cocopeat:1 perlite;T4=1 cocopeat:1 perlite;T5=1 cocopeat:2 perlite;T6=1 cocopeat:3 perlite) has been use for cocopeat-perlite unsaturated conductivity determination. Results obtained were compared using van Genuchten–mualem model, van Genuchten–Burdine and Brooks-and-Corey model with RETC software. Increase in perlite ratio, increases the hydraulic conductivity changes rate as the porosity in substrate increase, thus increase in plant roots aeration. T2 and T3 served as aeration improvement for cocopeat medium without rapid water loss in crop cultivation. In comparing results in Brooks-and-Corey and van Genuchten-Mualem, the derivation of hydraulic conductivity is increases as approaching to saturation point. However, to obtain accurate results when n is larger than 2, the van Genuchten model was preferable due to no bubbling pressure effect that may resulting in discontinuity happened near slopes at saturation point.
Keywords: cocopeat; hydraulic conductivity; perlite; RETC software; soilless culture; unsaturated hydraulic conductivity